Peran Teknologi Pendidikan dalam Meningkatkan Keterampilan Vokasional di Sekolah Menengah Kejuruan (SMK): Tinjauan Literatur Sistematis Berbasis Evidence-Based Practices (2021–2025) - Telaumbanua, Aprianus (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Digital transformation and the evolving demands of industry require Vocational High Schools to produce graduates who not only master specific technical skills, but are also adaptable to technological advancements, demonstrate procedural precision, and are capable of working within digitally driven systems. Educational technology is increasingly viewed as a strategic instrument for strengthening vocational learning; however, empirical evidence regarding its effectiveness remains fragmented and has not yet been systematically integrated. This article presents a systematic literature review of studies published between 2021 and 2025 on the role of educational technology in enhancing vocational skills in SMK and comparable TVET contexts. The review was conducted using an evidence-based practices (EBP) framework, with reporting guided by the PRISMA 2020 guidelines. Of the initial 405 publications identified, 196 articles were retained after the screening stage, 64 articles underwent full-text review, and 20 studies met the inclusion criteria for thematic analysis. The findings indicate that digital simulations, virtual reality (VR), augmented reality (AR), mobile learning, and learning analytics significantly contribute to improvements in psychomotor and procedural skills, training efficiency, and learning motivation. However, the effectiveness of technology is highly dependent on its alignment with competency objectives, instructional design grounded in cognitive load management, and the use of valid performance-based assessments. This article proposes both a conceptual framework and an implementation framework to support SMK in integrating educational technology in a sustainable and evidence-based manner.